Saprochaete clavata Invasive Infections - A New Threat to Hematological-Oncological Patients - Buchta, Vladimir; Bolehovská, Radka; Hovorková, Eva; Cornely, Oliver A; Seidel, Danila; Žák, Pavel (Frontiers in microbiology, 2019)
BACKGROUND: Saprochaete clavata (formerly Geotrichum clavatum, now proposed as Magnusiomyces clavatus) is a filamentous yeast-like fungus that has recently been described as an emerging pathogen mostly in patients with acute leukemia. METHODS: This is a retrospective study of patients diagnosed with proven and probable S. clavata infection at the University Hospital, Hradec Králové, Czechia between March 2005 and December 2017. Previous cases were identified from the literature and FungiScope® database. RESULTS: Six new cases (5 females, 1 male) of blood-stream S. clavata infections at the hemato-oncological department were described including epidemiological data of additional 48 patients colonized with the species. Overall, 116 strains of S. clavata were isolated from different clinical specimens of 54 patients; most of them belonged to the respiratory tract (60.3%). S. clavata was the most frequent species among arthroconidial yeasts (Trichosporon, Galactomyces, Magnusiomyces) recovered from the blood. All our patients with S. clavata infection had profound neutropenia, a central venous catheter, broad-spectrum antibiotics and antifungal prophylaxis; four had a history of a biliary tract system disease. The diagnosis was based on a positive blood culture in all patients. Four patients died of multiorgan failure and sepsis despite treatment with lipid-based amphotericin B and/or voriconazole. From the literature and FungiScope database, 67 previous cases of S. clavata infections were evaluated in context of our cases. CONCLUSION: Saprochaete clavata infection represents a life-threatening mycosis in severely immunocompromised patients. The successful outcome of treatment seems to be critically dependent on the early diagnosis and the recovery of underlying conditions associated with immune dysfunction or deficiency.
Keywords: fungemia; leukemia; therapy; FungiScopeTM; Magnusiomyces; Geotrichum; diagnosis; Saprochaete